FORMS OF ORGANIZATION OF TRAINING SESSIONS ON PHYSICAL AND COMBAT TRAINING OF CADETS - Ibadullaev Balkhoja (PEDAGOGS, 2024)
Abstract: Despite the presence of a certain number of scientific and methodological works on the formation of professionally applied physical training of cadets of the Ministry of Internal Affairs, the peculiarities of the structure of preparedness, the importance of motor abilities at various stages of readiness formation, the relationship between indicators of physical and technical preparedness have not yet been fully studied. The available data are scattered, and sometimes contradictory, which makes it difficult to generalize them theoretically and practically, and requires further research.